Analysis of Economic Factors Affecting Tax Revenues in Indonesia Over The 2019-2023 Period - Simbolon, Roberta Candy; Verilah, Tiara Alisya; Janiman, Janiman (International Journal of Business, Economics, and Social Development, 2025)
This analysis is carried out with the intention of examining economic factors that have an influence on tax revenue in Indonesia in the 2019-2023 timeframe. The variables analyzed include taxpayer compliance, unemployment rate, and Gross Domestic Product (GDP). The approach applied is quantitative through multiple regression analysis to analyze the relationship of all these variables. The results of the analysis prove that taxpayer compliance, unemployment rate and gross domestic product have a positive impact. Simultaneously, these three variables significantly affect tax revenue. The findings indicate that increasing tax compliance, reducing unemployment, and sustained economic growth can be effective strategies in increasing tax revenue in Indonesia. Therefore, a more inclusive tax policy and support for economic stability are crucial steps in optimizing tax revenue.